2020
DOI: 10.1039/d0ra07210a
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and separation of phosphorus as dicalcium phosphate dihydrate for fertilizer and livestock feed additive production from a low-grade phosphate ore

Abstract: A closed loop process was developed to extract phosphorus as dicalcium phosphate dihydrate from a low-grade ore for fertilizers and livestock feed additive production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The Na-EDTA leachant released on average 890 mg L −1 which was on average about 35%. The EDTA enables the formation of complexes with Fe 3+ ions, thus stabilizing them in the solution, which prevents their co-precipitation with phosphorus (Anawati and Azimi 2020 ). Here, in the leachates of fraction F2 the highest concentrations of trace elements were detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Na-EDTA leachant released on average 890 mg L −1 which was on average about 35%. The EDTA enables the formation of complexes with Fe 3+ ions, thus stabilizing them in the solution, which prevents their co-precipitation with phosphorus (Anawati and Azimi 2020 ). Here, in the leachates of fraction F2 the highest concentrations of trace elements were detected.…”
Section: Resultsmentioning
confidence: 99%
“…Ruan et al ( 2019 ) and Anawati and Azimi ( 2020 ) indicated that Al 2 O 3 + Fe 2 O 3 > 3 wt% and presence of impurities such as chlorine, fluorine, strontium, and heavy metals can affect P 2 O 5 recovery and unwanted crystallization of Al and Fe salts. These salts are characterized by low solubility and low plant availability (Kalmykova and Karlfeldt Fedje, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…[12,13] Hence phosphate form an integral part of agriculture industry, fertilizers, food additives and medicine. [14][15][16][17][18] However, if present in excess the phosphates can cause other health issues like abnormal renal function and can impact ecological balance. Excessive introduction of phosphate fertilizers into the water bodies can lead to algae proliferation [19] and ultimately eutrophication of aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we compare predicted bioaccessibilities using another geochemical modelling package, OLI Studio, and its built-in thermochemical framework (80 inorganic elements of the periodic table, and their associated aqueous species, as well as over 8000 organic species) [30]. As far as we are aware, this package has not been applied to the prediction of bioaccessibility, though it has been used in environmental applications [31][32][33].…”
Section: Introductionmentioning
confidence: 99%